A Secure Overlay Dynamic Multicast Network with Load Balancing for Scalable P2P Video Streaming Services - Kumbharkar, Prashant B; Sontakke, Trimbak Ramchandra (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
A creating mixed media Internet application P2p VIDEO-STREAMING over P2p system stops critical profit in adaptability. P2p VIDEO-STREAMING media substance conveyed in P2p organizes over open Internet still jam an issues of protection and licensed innovation rights. In this paper, we utilize SIP convention to build a safe application layer multicast overlay system, called SALMON. SALMON can secure all media conveyance ways against meddlers by means of elliptic-curve Diffie-Hellman (EDH) key trade on SIP flagging and AES encryption. Its burden adjusting overlay tree is additionally advanced from associate heterogeneity and stir of companion joining and leaving to minimize both administration debasement and dormancy. An execution results show SALMON’s expense viability in nature of protection ,stability from client churn, and great perceptual nature of destination PSNR values for versatile administrations over Internet.